Revitalizing Customer Experience through the Internet of Things : Integrating Customer Engagement and Campaign Effectiveness - Susanti, Putu Herny; Purnantara, I Made Hadi; Wardana, Miko Andi (Takaza Innovatix Labs Ltd., 2023)
This research study employs a quantitative approach to investigate the relationships among customer engagement (CEG), campaign effectiveness (CEF), IoT adoption, and their combined impact on customer experience (CEX) in the context of Bali's tourism industry. A random sample of 100 participants was selected from the target population, and structured surveys with Likert scale responses were used to collect data. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) was employed for data analysis, as it is well-suited for examining complex relationships among multiple variables. The study reveals significant direct relationships: CEG positively influences CEX, CEF positively influences CEX, and IoT adoption positively influences CEX. Additionally, there is a positive but relatively weaker relationship between CEG and IoT adoption and between CEF and IoT adoption. Indirect effects analysis shows that both CEG and CEF indirectly influence CEX through their impact on IoT adoption, although the latter relationship is relatively weaker. These findings have significant implications for Bali's tourism industry. Fostering customer engagement, effective marketing campaigns, and IoT adoption can enhance customer experiences, thereby increasing tourists' intention to revisit. This, in turn, can boost Bali's tourism sector, leading to economic growth and sustainability.